Antonio Agustín and the first Spanish translation of the Odyssey (Minerva, 2017)
Building on documentary, historical and palaeographic evidence, this paper argues that it was Antonio Agustín, along with Juan Paéz de Castro, who revised the Spanish translation of the Odyssey by Gonzalo Pérez, Philip II´s secretary.
Keywords: Antonio Agustín; Odyssey; manuscripts; Spanish hellenists